Two Simple Analog Multiplier Based Linear VCOs Using a Single Current Feedback Op-Amp - Bhaskar, Data R.; Senani, Raj; Singh, Abdhesh K.; Gupta, Shanti S. (Scientific research, 2010)
Two simple voltage-controlled-oscillators(VCO) with linear tuning laws employing only a single current feedback operational amplifier (CFOA) in conjunction with two analog multipliers(AM) have been highlighted. The workability of the presented VCOs has been demonstrated by experimental results based upon AD844 type CFOAs and AD534 type AMs
Keywords: Voltage-Controlled Oscillators; Current-Mode Circuits; Analog Multipliers; Current Feedback Op-Amps